Efficient single-strand break repair requires binding to both poly(ADP-Ribose) and DNA by the central BRCT domain of XRCC1 - Polo,LM; Xu,Y; Hornyak,P; Garces,F; Zeng,Z; Hailstone,R; Matthews,SJ; Caldecott,KW; Oliver,AW; Pearl,LH (Cell Reports, 2019)
XRCC1 accelerates repair of DNA single-strand breaks by acting as a scaffold protein for the recruitment of Polβ, LigIIIα, and end-processing factors, such as PNKP and APTX. XRCC1 itself is recruited to DNA damage through interaction of its central BRCT domain with poly(ADP-ribose) chains generated by PARP1 or PARP2. XRCC1 is believed to interact directly with DNA at sites of damage, but the molecular basis for this interaction within XRCC1 remains unclear. We now show that the central BRCT domain simultaneously mediates interaction of XRCC1 with poly(ADP-ribose) and DNA, through separate and non-overlapping binding sites on opposite faces of the domain. Mutation of residues within the DNA binding site, which includes the site of a common disease-associated human polymorphism, affects DNA binding of this XRCC1 domain in vitro and impairs XRCC1 recruitment and retention at DNA damage and repair of single-strand breaks in vivo.